Distributed renewable energies for off-grid communities : strategies and technologies toward achieving sustainability in energy generation and supply - El Bassam, Nasir (Elsevier, 2013)
Energy is directly related to the most critical economic and social issues which affect sustainable development such as mobility, food production, environmental quality, regional and global security issues. Two-thirds of the new demand will come from developing nations, with China accounting for 30%. Without adequate attention to the critical importance of energy to all these aspects, the global, social, economic and environmental goals of sustainability cannot be achieved. Indeed the magnitude of change needed is immense, fundamental and directly related to the energy produced and consumed na.